Design of Microclimate Monitoring and Graphical Interface System for Indoor Vertical Hydroponic Based on User-Centered Design Technique - Nanda, Muhammad Achirul; Amaru, Kharistya; Sophia Dwiratna; Jamaludin, Silmi Fauzan Yusup (Jurnal Keteknikan Pertanian, 2025)
Monitoring microclimate conditions, including temperature, humidity, and light intensity, is crucial for maintaining plant health and productivity in vertical indoor hydroponic systems. These conditions directly influence essential physiological processes such as photosynthesis and respiration, affecting growth and yield quality. Manual monitoring methods often suffer from inefficiencies such as slow data collection, operator dependency, and human error. This can delay responses to sudden microclimate changes, leading to plant stress and reduced productivity. This study aims to design a real-time microclimate monitoring and graphical interface system for indoor vertical hydroponics using a User-Centered Design (UCD) approach. The system integrates DHT11 and BH1750 sensors to measure temperature, humidity, and light intensity, respectively, with data processing performed using a Raspberry Pi 3 Model B+. The system performance was evaluated over 24 h using the root mean square error (RMSE) and accuracy metrics. Based on this analysis, the RMSE values for temperature, humidity, and light intensity were 2.398, 1.483, and 392.225, respectively, with an overall accuracy of 97.33%, demonstrating high reliability. Two interface prototypes, Design A and Design B, were developed using distinct visual approaches and evaluated by ten respondents across six criteria: appearance, color, layout, information, icon, and font. Design A outperformed Design B, achieving a higher average score (49 versus 43.4), reflecting its superior clarity and intuitive design. These findings highlight the potential of the proposed system to enhance microclimate management and optimize plant growth in indoor vertical hydroponics.